Increasing Repurchase Intention: The Mediating Role of Utilitarian Value and Experience in Perceived Ease of Use - Imbayani, I Gusti Ayu; Anggraini, Ni Putu Nita; Novarini, Ni Nyoman Ari (Universitas Pendidikan Ganesha, 2025)
Business actors, particularly micro, small, and medium enterprises (MSMEs), play a pivotal role in economic development. However, the performance of women-led MSMEs remains suboptimal. This study addressed the gap by examining online repurchase behavior in the context of female-managed MSMEs in Bali, given the increasing adoption of m-commerce. Although the online purchasing industry has grown rapidly, particularly through mobile platforms, the factors influencing consumer repurchase behavior remain inadequately understood, with existing literature showing inconsistent findings. This study aimed to analyze the impact of perceived ease of use, utilitarian value, and customer experience on repurchase intention. A total of 140 respondents were selected using purposive sampling, and data were analyzed using Structural Equation Modeling (SEM). The findings revealed that perceived ease of use significantly influenced both utilitarian value and customer experience. Customer experience had a direct positive effect on repurchase intention and mediated the relationship between perceived ease of use and repurchase intention. In contrast, utilitarian value did not significantly affect repurchase intention and failed to mediate the effect of perceived ease of use. Theoretically, the study contributes to the refinement of the Technology Acceptance Model (TAM). Practically, it provides strategic insights for women-led MSMEs in Bali to enhance business sustainability through improved digital engagement.